Application of the Peer Tutor Learning Model to Improve Learning Outcomes of Fifth Grade Students at Cintawana Elementary School in Mixed Integer Computing Operations - Sri Hernawati (PT FORMOSA CENDEKIA GLOBAL, 2023)
The main problem in this study is the low learning outcomes of fifth grade students at SDN Cintawana in solving mixed integer arithmetic operations. The formulation of the problem in this study is: